Adsorption properties of Merrifield-bCCA chelating resins: a new alternative for Pb2+ removal from water† - Gracia-Elías, José; Ocho-Terán, Adrián; López-Maldonado, Eduardo; Pérez-Sicairos, Sergio; Trujillo-Navarrete, Balter; Rivero, Ignacio; Zizumbo-López, Arturo; Martinez Quiroz, Marisela (My University, 2025)
In this work, five new chelating resins (MRnBz) functionalized with N-benzyl bis(carbamoyl)carboxylic acid molecules (BzbCCA) on their surface were prepared to study the metal ion (Mn+) adsorption properties in water. MRnBz resins were characterized by FTIR, TGA, FESEM and EDS. The surface charge as a function of pH and the chemical adsorption of Mn+ on the surface were evaluated through zeta potential (z) measurements. The Mn+ adsorption capacity of MRnBz resins was evaluated using Pb2+, Cu2+, Cd2+, and Ni2+ mixture model solutions at low concentrations. MRnBz resins displayed selective adsorption of Pb2+ even in the presence of a molar excess of other cations, due to the intrinsic affinity and selectivity of BzbCCA molecules for this metal ion. The adsorption isotherms of Pb2+ showed that the adsorption capacity of MRnBz resins was influenced by the spacer chain length. In addition, the resins were characterized by FTIR, TGA, FESEM and EDS after the Mn+ adsorption process, confirming the Mn+ loading on the resin surface.
Royal Society of Chemistry
Keywords: Adsorption; Chelating resins; Campus Tijuana